Penggunaan Media Buku Cerita Bergambar Untuk Meningkatkan Kemandirian Anak Kelompok B Di Tk Katolik Xaverius Kairagi Manado - Kapita, Anastasia (Peneliti.net, 2023)
Children's independence in Xavier Catholic Kindergarten is still low. This is the background for carrying out this research. The aim of this research is to describe the use of picture storybook media to increase children's independence. The research method used is Classroom Action Research model Kemmis and Mc. Taggart is carried out twice in cycles with the steps namely planning, implementation, observation and reflection. The subjects of this research were the Xaverius Kairagi Manado Catholic Kindergarten group B, totaling 17 children. The data collection techniques used were observation and field notes as well as data analysis using assessment techniques in kindergarten. The results of the research showed that the first cycle was 58.82% and the second cycle experienced an increase after improvements were made to 100%. It was concluded that the use of picture storybook media can increase children's independence at the Xaverius Kairagi Manado Kindergarten